Penerapan Pewarnaan Graf Menggunakan Algoritma Welch Powell Pada Penempatan Kamar Mahasiswa (Studi Kasus : Asrama F Universitas Islam Darul ‘Ulum) - Agus Mutia; Siti Amiroch (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
The allocation of student dormitory rooms often faces potential conflicts if not managed properly, especially when students from the same study program are assigned to the same room. This study aims to optimize the room assignment of students in Dormitory F at Universitas Islam Darul ‘Ulum by applying graph theory, specifically graph coloring using the Welch-Powell algorithm. Each student is represented as a vertex, and edges connect students from the same study program, indicating they should not share a room. The Welch-Powell algorithm colors the graph by ordering vertices in descending order of degree and assigning colors so that no two adjacent vertices share the same color. The results show that 14 students from 8 different study programs were successfully grouped into 4 rooms, ensuring no students from the same program share a room. This method effectively reduces potential conflicts, fosters an inclusive and heterogeneous dormitory environment, and broadens inter-program student interactions. The approach provides a practical solution for dormitory management to arrange room assignments efficiently and harmoniously.